Revision of Asytesta Pascoe, 1865, with comments on the phylogeny of the Indo-Australian crowned weevils (Coleoptera: Curculionidae: Cryptorhynchinae) - Setliff, Gregory P. (Zootaxa, 2012)
The Indo-Australian crowned weevil genus Asytesta Pascoe, 1865 is revised. Forty-one species are recognized, including18 that are new: A. alexandriae, A. alexriedeli, A. allisoni, A. biakana, A. cheesmanae, A. concolora, A. emarginata, A.fayae, A. frontalis, A. gressitti, A. julieae, A. marginalis, A. morobeana, A. sedlaceki, A. thompsoni, A. tuberculata, A.vivienae, and A. woodlarkiana, new species. One subspecies, A. lugubris bidentata Voss is elevated to species status, A.bidentata Voss, new status. Four species are newly synonymized: A. circulifera Lea, 1928 = A. rata Heller, 1910, A.definita Faust, 1898 = A. humeralis Pascoe, 1865, A. granulifera Lea, 1928 = A. aucta Faust, 1898, and A. setipes Lea,1928 = A. lugubris Heller, 1895 new synonyms. Six new species groups are proposed. Lectotypes are designated for 18species. Two species are transferred from Asytesta to other genera: A. maura Pascoe to Microporopterus Lea and A.ypsilon Heller to Meroleptus Faust, new combinations. A checklist and key for all crowned weevil genera, key to speciesgroups and species of Asytesta, adult habitus illustrations, distribution maps, and line drawings of diagnostic charactersare provided.A phylogeny for the genus based on 82 adult morphological characters (187 states) for 41 ingroup taxa is alsopresented. All genera and species of the crowned weevil group as redefined here (including Cyamomistus Heller,Eudyasmus Pascoe, Glochinorhinus Waterhouse, Nothotragopus Zimmerman, Panopides Pascoe, and Zygara Pascoe),were included in the analysis to test the monophyly of Asytesta. Monophyly of Asytesta was supported only with thesynonymy of the monotypic genus Zygara. Accordingly, Zygara is a new junior synonym of Asytesta and Zygara doriae (Kirsch) is returned to its original combination with Asytesta; A. doriae Kirsch resurrected status.